Link Between Innovation Strategy, Innovation Culture, and SMEs Innovation Performance in Indonesia - Azizah, Siti Nur; Solichin, Much. Riyadus; Susilowati, Ika (AIBPM Publisher, 2023)
This study aims to investigate the impact of innovation strategy on small and medium-sized enterprises (SMEs), focusing on the mediating role of innovation culture. There needs to be more prior literature on innovation performance in small and medium enterprises (SMEs) in Indonesia, particularly in terms of serving as benchmarks for assessing SME success. A study utilizing a questionnaire was undertaken to gather data from small and medium-sized enterprises (SMEs) located in Central Java, Indonesia. One hundred fifty surveys were collected and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The investigation findings indicate that both the proactive and the growth strategies have a good impact on the culture of innovation. Innovation culture was found to have a positive effect on innovation performance. Even though the culture of innovation mediates the relationship between proactive strategy and innovation performance, innovation culture still needs to be proven to mediate the relationship between growth strategy and innovation performance.